VIRTUAL PROJECT «UKRAINIAN ART IN THE GLOBAL SPACE: NAMES AND FATES»: EXPERIENCE OF COMMUNICATION WITH EDUCATORS - Komarovska, Oksana (Theoretical and Methodical Problems of Children and Youth Education, 2024)
The article highlights the importance of a Ukraine-centered approach of arts education and the formation of a Ukrainian artistic mindset. Practical scientific and methodological achievements in this direction are illustrated through the concept and nationwide implementation of an educational Ukrainian art project with feedback mechanisms. The purpose of the article is to reflect on the progression of a prolonged art project for teachers in general secondary education, aligning with a Ukraine-centered focus on art education for students. The content dynamics of the educational art project for teachers are systematized by types of art within the educational content area (music, visual arts, architecture, theater, etc.), museum pedagogy, and the art of the Ukrainian diaspora across various periods. The need for Ukraine-centered communication with educators is emphasized as a means of supporting the assertion of Ukrainian content in artistic communication with students; counteracting anti-Ukrainian information warfare tactics (forced Russification, the imposition of a cultural inferiority complex, “erasing” Ukrainian identity). The article outlines the effectiveness of integrating project materials into art lessons by teachers. It describes the evolution of teachers’ attitudes toward the need to change the content strategy of arts education post-February 2022, shifting from confusion and disorientation regarding artistic content to increased confidence and independent creative exploration. Methods applied include continuous surveys of respondents participating in the cycle of Ukraine-centered educational art webinars, observation of content within professional communities on social media, comparative analysis of results, and forecasting.